Analgin Induced Fixed Drug Bullous Eruption – ACase Report - K.M, Vinod; C, Dipsanker; K.V, Ramesh; G, Girish; M, Beulah (Indian Journal of Pharmacy Practice)
Cutaneous drug eruptions are one of the most common types of adverse reaction to drug therapy, with an overall incidence rate of 2–3% in hospitalized patients. The prevalence of drug eruptions has been reported to range from 2-5% for inpatients and greater than 1% for outpatients. Fixed drug eruptions (FDE) may account for as much as 16-21% of all cutaneous drug eruptions. Most studies report fixed drug eruptions to be the second or third most common skin manifestation of adverse drug events. The actual frequency may be higher than current estimates, owing to the availability of a variety of over-the-counter medications and nutritional supplements that are known to elicit fixed drug eruptions. Certain classes of drugs with cross-reactions within a class have been reported to elicit a fixed drug eruption with quinolones and with non-steroidal anti-inflammatory agents. The most common cause of FDE is trimethoprim-sulfamethoxazole followed by analgin.